Kajian Yuridis Terkait Hak-Hak Tersangka Menurut Hukum Positif - Ridwan Ridwan; Ichwan Setiawan (Syntax Literate, 2023)
The institution appointed to tackle crimes or violations that occur in the community is the police agency. As stated in the criminal procedure code (KUHAP), the police agency is given the authority to conduct investigations. The investigation process is carried out on the suspects who are suspected of having committed a criminal act that occurred. In an effort to prove that a person is suspected of having committed a criminal act, law enforcement officials must pay attention to the rights of suspects as stipulated in applicable law. Based on the above, the problem that will be discussed in this writing is about what rights are obtained by suspects according to the Criminal Procedure Code and Human Rights as a manifestation of protecting dignity and dignity as human beings. As for the research method used is a normative research method which of course focuses on literature research to obtain secondary data from legal materials. The normative approach is carried out by reviewing the provisions or applicable laws and regulations. The results of the study that the rights of suspects in the Criminal Justice System in Indonesia have officially received legal recognition as stipulated in Law Number 39 of 1999 concerning Human Rights and Law Number 8 of 1981 concerning Criminal Procedure Law known as the Code of Criminal Procedure (KUHAP) as respect as a complete human being, who has dignity and dignity.